TCH-010 Development of a Topical Lidocaine Sterile Formulation 20% (W/V). (12th March 2013) - Trindade, P; Mateus, D; Gonçalves, H; Salgado, A; Almeida, A; Machado, P; Marto, J; Silva, A; Eleutério, C; Melo Gouveia, A
Abstract : Background: The topical use of concentrated solutions of lidocaine (4 to 20%), which are usually unavailable, has been reported for microvascular surgery. Vasospasm is known to have an adverse effect on the survival of free tissue transfers. Prolonged vasoconstriction decreases blood flow to the flap and promotes thrombosis at the anastomotic site. The wide availability and rapid effect of topically applied lidocaine is used by many surgeons to prevent and correct vasospasm. Purpose: To compound a sterile 20% (w/v) lidocaine solution physicochemically and microbiologically stable for topical application during surgery. Materials and Methods: Three batches of a 20% (w/v) sterile lidocaine solution were prepared using two sterilisation steps: autoclaving followed by filtration (0.22 µm) inside a horizontal laminar flow hood. Packaging in 10 ml dropping containers prevents intravenous administration and ensures a maximum safe dose (2 g). For physicochemical and microbiological stability studies, samples were stored in the dark at 5 ± 3°C and 22 ± 3°C, for 15 days. Sterility tests and bacterial endotoxins assays were performed (Ph. Eur.). Samples were collected and characterised on days 0 (T0), 7 (T7) and 15 (T15). Colour, odour, appearance, pH, osmolarity, density and lidocaine hydrochloride content were analysed. Results: Throughout the study, the 20% (w/v) lidocaine hydrochloride solutions remained clear, colourless, limpid and odourless. The pH of the solutions stored at 5 ± 3°C was 3.6 ± 0.04 (T0), 3.8 ± 0.08 (T7), 3.9 ± 0.02 (T15), and 3.6 ± 0.04 (T0), 3.9 ± 0.02 (T7), 4.0 ± 0.03 (T15) for the solutions maintained at 22 ± 3ºC. The HPLC analyses showed that the lidocaine hydrochloride content was maintained (90–110%) after 15 days in all conditions tested. Density and osmolality remained constant, i.e. 1.0049 ± 0.0036 g/cm 3 and 1175.3 ± 20.2 mOsm/kg, respectively (n = 3). The three batches proved to be sterile and endotoxins-free during the study. Conclusions: The lidocaine hydrochloride solution proved to be physicochemically and microbiologically stable for 15 days stored in the dark. No conflict of interest.